2017
DOI: 10.1002/er.3908
|View full text |Cite
|
Sign up to set email alerts
|

An up to date review of continuously variable speed wind turbines with mechatronic variable transmissions

Abstract: Summary As a promising and potential alternative to conventional fixed or variable speed wind turbines, continuously variable speed wind turbines (CVSWTs) with variable transmissions offer improved power efficiency and enhanced power control capabilities. The CVSWTs can be generally achieved by adapting mechatronic variable transmissions in the turbine drive train for continuously variable speed operations for wind turbines. Therefore, this paper serves to provide an up to date and exhaustive review of the CVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The requirements on the classical wind turbine drive trains are getting more and stricter such as low cost and high reliability. However, these needs for pure large mechanical gearboxes lead to technological challenges in large gearboxes and highly stressed structural components like planetary carriers [1]. For example, the difficulties in today's 3 MW mutli-megawatt wind turbine gearboxes are related to internal gear fabrication, lubrication management and gearing corrections [2].…”
Section: Introductionmentioning
confidence: 99%
“…The requirements on the classical wind turbine drive trains are getting more and stricter such as low cost and high reliability. However, these needs for pure large mechanical gearboxes lead to technological challenges in large gearboxes and highly stressed structural components like planetary carriers [1]. For example, the difficulties in today's 3 MW mutli-megawatt wind turbine gearboxes are related to internal gear fabrication, lubrication management and gearing corrections [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that pumped storage stations w to 70% can be operated efficiently by applying variable-speed technology [18]. To r the variable-speed operation of hydropower plants and maintain the constant-freq connection to the grid-the power electronic component frequency converter, wh more commonly used in wind power plants-is used [19]. Then, several variablemethods are proposed, and the structures of the two connection methods of va speed hydropower units, which are more frequently used at present, are shown in F 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbines (WTs) are typically exposed to continuously varying loads, large and continuous output power fluctuations and continuously varying thermal loading conditions EC 37,8 because of the stochastic nature of highly variable and unpredictable wind speeds. Currently, the WTs are typical two configurations: the electrically-based variable speed WTs and the continuously variable speed wind turbines (CVWTs) (Yin, 2019;Yin et al, 2016;Yin, 2017;Yin et al, 2019). The state art review of the CVWTs hydraulic transmissions with elaborates on the typical CVSWTs with hydrostatic transmission, hybrid hydraulic transmission and hydrodynamic transmission has been focused by Yin (2019).…”
Section: Introductionmentioning
confidence: 99%
“…A hydro-viscous transmission-based maximum power extraction control for CVWTs to increase the power capture has been presented in Yin et al (2016). The CVSWTs with different mechatronic transmission topologies regarding basic configurations, dynamic characteristics, control principles and experimental or simulation results has been reviewed in Yin (2017). The current status and prospects of CVWTs has been systematically reviewed in Yin et al (2019), which indicate the feasibility of applying CVSWTs, as well as the high potential of using the hydro-viscous transmission in the wind power industry.…”
Section: Introductionmentioning
confidence: 99%